Role of Coastal Vegetation Belts in Mitigating Tsunami Waves: Bibliometric Analysis, Numerical, and Spatial Analysis - Usman, Fadly; Murakami, Keisuke; Wijatmiko, Indradi; Rokman, Mauhibur; Nabila, Meutia Aisyah (Universitas Pendidikan Indonesia (UPI), 2025)
Tsunami is a catastrophic natural disaster that is difficult to predict and often results in significant loss of life and property damage. This study examines the role of coastal vegetation belts in mitigating tsunami wave impacts through numerical and spatial analyses. This study also used bibliometric analysis to support the discussion. Numerical simulations using CADMAS Surf 2D were conducted for various scenarios to assess the effect of vegetation belts on wave speed and height. Spatial analysis using ArcGIS was employed to map tsunami-affected areas, and grid-cell analysis was used to calculate the volume of water entering inland areas during a tsunami event. The results demonstrate that vegetation belts with specific thicknesses and densities significantly reduce wave speed and height, thereby mitigating tsunami energy as it approaches land. These findings emphasize the critical role of vegetation belts in coastal management strategies. Future research should explore integrating natural barriers with artificial infrastructure, such as embankments, to provide comprehensive protection against tsunami impacts.